1999
DOI: 10.1016/s1010-7940(99)00136-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and S100B levels in paediatric patients undergoing corrective cardiac surgery with or without total circulatory arrest

Abstract: (1) The TCA group have prolonged rises of IL-6, IL-8 and S100B. (2) The TCA group generates significantly lower complement. (3) Astroglial injury, seen after surgery, may, in part, be cytokine mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 22 publications
0
26
2
Order By: Relevance
“…While on-pump without CA surgery was associated with an increase in serum S100 protein, a marker of cerebral injury [9] at 12 h and in CrCl, indicating impaired glomerular filtration [7] at 1 h post surgery when compared with onpump with CA, these effects were transient; at other time points, the results were similar in the two groups. Studies have shown that high levels of S100 and cerebral dysfunction after cardiac surgery may be cytokine mediated [22], but the bulk of the evidence points towards micro-emboli as the major cause of post-cardiac surgery cerebral dysfunction [9,23]. In a study comparing on-pump versus off-pump coronary surgery, we demonstrated that elevated S100 was strongly associated with retinal and cerebral micro-embolisation [9].…”
Section: Discussionmentioning
confidence: 74%
“…While on-pump without CA surgery was associated with an increase in serum S100 protein, a marker of cerebral injury [9] at 12 h and in CrCl, indicating impaired glomerular filtration [7] at 1 h post surgery when compared with onpump with CA, these effects were transient; at other time points, the results were similar in the two groups. Studies have shown that high levels of S100 and cerebral dysfunction after cardiac surgery may be cytokine mediated [22], but the bulk of the evidence points towards micro-emboli as the major cause of post-cardiac surgery cerebral dysfunction [9,23]. In a study comparing on-pump versus off-pump coronary surgery, we demonstrated that elevated S100 was strongly associated with retinal and cerebral micro-embolisation [9].…”
Section: Discussionmentioning
confidence: 74%
“…Cardiac surgery with CPB S100B increased, maximum at the end of CPB, also malondialdehyde concentration increased as a marker of radical-induced lipid peroxidation Ashraf et al, (1999) N ϭ 12 (neonates), N ϭ 12 (infants)…”
Section: Lia Sangtecmentioning
confidence: 97%
“…The maximum increase of serum S100B was found between 0 and 24 hours after cardiac surgery (AbdulKhaliq et al, 1999;Ashraf et al, 1999;Blomquist et al, 1997;Gao et al, 1999;Gazzolo et al, 1998;Jönsson et al, 1998;Lindberg et al, 1998;Linstedt et al, 2000;Rasmussen et al, 1999). In two studies an additional peak was detected after 48 hours (Jönsson et al, 1998;Rasmussen et al, 1999).…”
Section: Elisa Synx Pharmamentioning
confidence: 97%
“…14 Ashraf et al suggested that increased S100 protein levels after cardiac surgery may be cytokinemediated. 15 An elevated level of serum S100 in patients with an uneventful clinical outcome may provide evidence of subclinical injury, which may be due to diffuse microemboli and increased permeability of the BBB. 16,17 The BBB is normally not permeable to proteins.…”
Section: Discussionmentioning
confidence: 99%